Strategi Role Playing untuk Meningkatkan Kemampuan Berpikir Kritis dalam Pembelajaran Pendidikan Pancasila - Achmad Robi Afrilihadi; Berliana Dian Permatasari; Maulana Malik Ibrahim; Muhammad Japar; Yuyus Kardiman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Pancasila Education Learning requires innovative strategies to improve students' critical thinking skills. One effective method is role playing, particularly in the form of moot court, which allows students to engage directly in the simulation of law and democracy. This study uses a qualitative approach of a case study involving 36 students. Data were collected through interviews, non-participatory observations, and documentation that was analyzed by data reduction, data presentation, and conclusion drawn. The results of the study show, first, role playing significantly increases student involvement in learning. Second, students also show improvements in critical thinking, especially in the aspects of analysis, reflection, and argumentation. Third, hands-on experience in trial simulations helps students understand the legal process and democracy in a more contextual way. The findings reveal that role playing significantly increased student engagement and contributed to the development of critical thinking skills, particularly in the dimensions of analysis, reflection, and argumentation. Students were able to connect theoretical concepts with real-life cases, evaluate evidence more critically, and articulate arguments based on logic and facts. They also demonstrated greater awareness of multiple perspectives and improved confidence in presenting structured arguments. However, the study also identified several challenges, including limited preparation time, varied levels of participation, and difficulties in formulating evidence-based arguments. Despite these constraints, role playing proved to be an effective and innovative learning strategy that bridges theory and practice, providing students with contextual and meaningful experiences in understanding law and democracy. Therefore, role-playing simulations hold strong potential to be integrated more widely into Pancasila Education as a means of fostering critical, reflective, and democratic learners.